0031 Nlrp3 Inflammasome Mediates Il-18 And Il-18 Receptor Responses To Sleep Loss. (27th April 2018) - Johnston, A M; Niznikiewicz, M M; Gerashchenko, D; Strecker, R E; Basheer, R; Zielinski, M R
Abstract: Introduction: Interleukin (IL)-18 is a pro-inflammatory cytokine involved in immunity, behavior, and enhancing sleep. The nucleotide-binding domain leucine rich family pyrin containing 3 (NLRP3) inflammasome is a protein complex that activate the enzyme caspase-1, which converts the pro-forms of IL-18 and IL-1beta into their active forms. We previously found that the expression of NLRP3 inflammasome components, caspase-1 activity, and IL-1beta protein is enhanced in the somatosensory cortex by sleep deprivation. Herein, we determined the effects of sleep deprivation on IL-18 gene expression in the brain. Methods: NLRP3 knockout (KO) and wild-type (WT) control mice were sleep deprived for 6 h prior to dark onset or allowed to sleep ad libitum. Thereafter, mice were either perfused and brains were collected and processed for immunohistochemistry or rapidly dissected and somatosensory cortex, thalamus, and brainstem regions were flash frozen. Brain sections were double-labeled with anti-IL-18 and neuronal and glial-markers [anti-glial fibrillary acidic protein (astrocytes), and anti-CD11b (microglia)]. Percent change in the number of IL-18 immuno-reactive astrocytes and microglia were determined between treatments. Frozen tissues were processed and analyzed for IL-18, IL-18 receptor accessory protein (IL-18RAP), and IL-18 receptor 1 (IL-18R1) mRNA by real-time polymerase chain reaction. Results: IL-18 mRNA expression in the somatosensory cortex, thalamus, and brainstem was enhanced in WT (p<0.001 for all brain areas) but not NLRP3 KO mice after sleep deprivation. Conversely, IL-18RAP and IL-18R1 expression were attenuated after sleep deprivation in WT mice (p=0.002 and p=0.022, respectively) but not in NLRP3 KO mice. We also observed enhancements in the number of IL-18 immuno-reactive microglia in the same brain areas thus matching the mRNA expression findings. Conclusion: Our findings indicate that sleep deprivation enhances IL-18 in sleep-related brain areas and that the NLRP3 inflammasome, in part, contributes to this effect. Support (If Any): Veterans Affairs I01RX00928 (MRZ), I01BX001404 (RB), I01BX002774 (RES)